2019
DOI: 10.1002/pen.25146
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of electrospun keratin nanofiber membranes for air and water treatment

Abstract: Keratin proteins extracted from wool fibers by sulfitolysis were electrospun for the production of active nanofiber membranes (NFMs). The keratin NFMs were composited with nylon woven fabric for improving their mechanical properties as a filtration material. The prepared membranes were characterized in terms of morphology, pore size, contact angle, and performance of water and air permeability. Experimental data showed that most of investigated parameters were affected by the electrospinning time: that is, rou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 37 publications
0
22
0
1
Order By: Relevance
“…Alternative technologies involve nanofiltration, reverse osmosis, and enzymatic treatment. From this perspective, nanofibers represent the most promising material [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Alternative technologies involve nanofiltration, reverse osmosis, and enzymatic treatment. From this perspective, nanofibers represent the most promising material [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…However, the production of keratin membranes is difficult due to its insolubility in water and organic solvents, low viscoelastic properties, and low molecular weight 106 . Figoli et al 107 recommended membrane keratin for filtration applications. The study revealed filtration efficiency of the keratin membrane against microorganisms, heavy metals, and organic materials, as well as harmful gasses and air.…”
Section: Biodegradable Natural Polymer Based Nanofibresmentioning
confidence: 99%
“…Keratins are versatile proteins for the production of flexible films, sponges, fibers, and nanofibers. In particular, pure keratin can be transformed into nanofibers by electrospinning from solutions of solvents, such as formic acid [88] and 1,1,1,3,3,3-hexafluoro-2-propanol [53]; on the contrary, keratin-based nanofibers have been obtained from water solutions by the addition of synthetic water-soluble polymers, like poly(ethyl oxide) [89], polyvinyl alcohol [90], polyvinylpyrrolidone [91], and polycaprolactone [53].…”
Section: Natural Vs Synthetic Fibersmentioning
confidence: 99%